If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -12x + -8 = -8 Reorder the terms: -8 + 6x + -12x = -8 Combine like terms: 6x + -12x = -6x -8 + -6x = -8 Add '8' to each side of the equation. -8 + 8 + -6x = -8 + 8 Combine like terms: -8 + 8 = 0 0 + -6x = -8 + 8 -6x = -8 + 8 Combine like terms: -8 + 8 = 0 -6x = 0 Solving -6x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-6'. x = 0 Simplifying x = 0
| -3(4z+5)=-15-20+3z | | 6-(3+1)*5=17 | | 3xa+8x-6x+9=2 | | 105=-5(x-10)+15 | | -60+4g=14g | | 84=7(x+7) | | -18z+14z+-20z+8z=16 | | 2x^2=960 | | 28xy^7/32xy^12 | | -6-4=-7a+11 | | -5(-2)+(6(-2)-4)= | | 6-(3*1)+5-1=17 | | -177+5x=23-5x | | 15xcos(55)= | | z=y-m+x | | 4(p+5)+4=10p-1 | | 12=7a | | 8i/3-5i | | -6=x/1.5 | | 3(4w-1)=18 | | -3-9b=-147 | | 7(x+8)=9 | | 3m-m+2m+3m-6m=9 | | f(-5b)=7x+5 | | -[10z(20z+7)]= | | 23x-5+22x+5=180 | | 3xy^4/9xy | | 14y/8x=12 | | w/-23=15 | | 2x+2=19-3x+4x | | 23x-5+22x+5=189 | | 3xy4/9xy |